HUBUNGAN ANTARA PENGETAHUAN BAHAYA MEROKOK DENGAN KEINGINAN BERHENTI MEROKOK PADA SISWA SMP DI KOTA BANDAR LAMPUNG - Hetti Rusmini (JKM (Jurnal Kebidanan Malahayati), 2020)
ABSTRACT Background: The results of a survey in Indonesia in 2014 of 4,313 grade 7-9 students with an age range of 13-15 years (2029 boys and 2284 girls) at the selected schools, found that 18.3% were active smokers. Lampung is in the 13th position with a percentage of 12.1%. Objective: the research was to determine the relationship between knowledge of the dangers of smoking and the desire to quit smoking in junior high school students in Bandar Lampung. Methods: The research design used in this study is an analytic survey, by conducting a questionnaire about the dangers of smoking on 490 junior high school students in Bandar Lampung.  Results: the research showed that 287 students (58.5%) of junior high school students in Bandar Lampung were smokers. Where as many as 252 student smokers (87.8%) know the dangers of smoking. And as many as 273 student smokers (95.1%) have the desire to quit smoking. Conclusion is that there is a significant relationship between knowledge of the dangers of smoking and the desire to quit smoking in junior high school students in Bandar Lampung.Suggestion There needs to be an effort to strengthen smoking in every school so that students understand the dangers of smoking and are motivated to stop smoking Keywords: The danger of smoking, the desire to quit smoking, cigarettes, school students ABSTRAK Latar Belakang: Hasil survei di Indonesia tahun 2014 terhadap 4.313 siswa kelas 7-9 dengan rentang usia 13-15 tahun (laki-laki berjumlah 2029 dan perempuan berjumlah 2284) pada sekolah yang dipilih, ditemukan  bahwa terdapat 18,3% perokok aktif. Lampung terletak pada urutan ke-13 dengan persentase sebanyak 12,1 %.Tujuan Penelitian untuk mengetahui hubungan pengetahuan bahaya merokok terhadap keinginan berhenti merokok pada siswa SMP di Kota Bandar Lampung.Metode yang digunakan pada penelitian ini bersifat analitik survey, dengan  melakukan kuisioner tentang bahaya merokok  pada 490 siswa SMP di Bandar Lampung.Hasil penelitian menunjukkan bahwa 287 siswa (58,5%) Siswa SMP di Kota Bandar Lampung merupakan perokok. Dimana sebanyak 252 siswa perokok (87,8%) mengetahui bahaya merokok. Dan sebanyak 273 siswa perokok (95,1%) memiliki keinginan untuk berhenti merokok.Kesimpulan yaitu terdapat Hubungan bermakna antara pengetahuan bahaya merokok terhadap keinginan berhenti merokok pada Siswa SMP di Kota Bandar Lampung.Saran perlu dilakukan upaya penyukuhan ttg bhy merokok ke setiap sekolah2 supaya para siswa memahami bahaya merokok dan termotivasi utk berhenti merokok Kata Kunci: Bahaya merokok, keinginan berhenti merokok, rokok, siswa sekolah